Consider the pons: bridging the gap on sensory prediction abnormalities in schizophrenia. Issue 11 (November 2022) - Abram, Samantha V.; Hua, Jessica P.Y.; Ford, Judith M.
Abstract : A shared mechanism across species heralds the arrival of self-generated sensations, helping the brain to anticipate, and therefore distinguish, self-generated from externally generated sensations. In mammals, this sensory prediction mechanism is supported by communication within a cortico-ponto-cerebellar-thalamo-cortical loop. Schizophrenia is associated with impaired sensory prediction as well as abnormal structural and functional connections between nodes in this circuit. Despite the pons' principal role in relaying and processing sensory information passed from the cortex to cerebellum, few studies have examined pons connectivity in schizophrenia. Here, we first briefly describe how the pons contributes to sensory prediction. We then summarize schizophrenia-related abnormalities in the cortico-ponto-cerebellar-thalamo-cortical loop, emphasizing the dearth of research on the pons relative to thalamic and cerebellar connections. We conclude with recommendations for advancing our understanding of how the pons relates to sensory prediction failures in schizophrenia. Highlights: A basic mechanism common to all species heralds the arrival of self-generated sensations, allowing animals to distinguish between self-generated and externally generated sensations. Importantly, this mechanism is impaired in schizophrenia. In mammals, the distinction between self-generated and externally generated sensations depends on rapid and unconscious communication between regions within a cortico-ponto-cerebellar-thalamo-cortical loop. The pons is the principal hub through which descending cortical signals relaying expected sensory experiences are transmitted to the cerebellum, where they are compared with actual sensory feedback. Abnormal connections between various nodes in the cortico-ponto-cerebellar-thalamo-cortical loop are well documented in schizophrenia, although relatively sparse attention has been paid to the pons, despite its centrality in this loop. Consideration of the full cortico-ponto-cerebellar-thalamo-cortical loop is critical for characterizing sensory abnormalities in schizophrenia.